Efficient and configurable data transport protocol for grid computing - WANG Ji-gang1; GU Guo-chang1; MA Chun-guang1; ZHONG Wei-dong2 (Tongxin xuebao)
The demands of grid computing were difficulty satisfied by mainstream data transfer protocols at present.Considering the situation,an efficient and configurable data transfer protocol ECUDP for grid computing was proposed.ECUDP was based on standard UDP（user datagram protocol）,but with a collection of optimizations that met the chal-lenge of providing configurability and reliability while maintaining performance that met the communication require-ments of demanding applications.Experiment results show that ECUDP performs extremely efficiently in various grid computing scenarios and performance analytical model is able to provide good estimates of its performance.